2016
DOI: 10.1016/j.jedc.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of innovation networks from R&D cooperation with endogenous absorptive capacity

Abstract: This paper extends the existing literature on strategic R&D alliances by resenting a model of innovation networks with endogenous absorptive capacity. The networks emerge as a result of bilateral cooperation over time between firms occupying different locations in the knowledge space. Social capital is ignored, and firms ally purely on the basis of knowledge considerations. Partner selection is driven largely by absorptive capacity which is itself influenced by cognitive distance and investment allocation betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 40 publications
0
17
0
1
Order By: Relevance
“…ABMs respond to this by describing one or multiple populations of agents with internal diversity in terms of bounded rationality and other‐regarding preferences (De Grauwe, 2011). In addition, many models include social interactions in terms of information sharing or behavioral spillovers (Powell, 1998; Savin & Egbetokun, 2016). This allows addressing important behavioral phenomena, such as conformism, status seeking, and imitation.…”
Section: Agent‐based Modelingmentioning
confidence: 99%
“…ABMs respond to this by describing one or multiple populations of agents with internal diversity in terms of bounded rationality and other‐regarding preferences (De Grauwe, 2011). In addition, many models include social interactions in terms of information sharing or behavioral spillovers (Powell, 1998; Savin & Egbetokun, 2016). This allows addressing important behavioral phenomena, such as conformism, status seeking, and imitation.…”
Section: Agent‐based Modelingmentioning
confidence: 99%
“…Ivan reported that the cognitive distance, cognitive ability, and communication mechanism of the R&D innovation subject are the main factors in a collaborative network structure. The dynamic cooperation is formed through the selection mechanism of knowledge space [21]. Gay and Dousset also stated that the frequency of the entry and exit for enterprises leads to changes to the network, and that the time and spatial boundaries of network construction change as a result [22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In some models, knowledge is exchanged via a barter trade mechanism, meaning that knowledge will only be exchanged if all partners involved can somehow benefit from the exchange (e.g., Cowan and Jonard 2004 ), whereas in others, knowledge may flow freely (see also Klarl 2014 ; Morone and Taylor 2009 , on these different diffusion or transfer mechanisms). In addition, many of the models with an economic focus also incorporate the absorptive capacity 3 of firms, which also influences the diffusion process (e.g., Cowan and Jonard 2004 ; Egbetokun and Savin 2014 ; Savin and Egbetokun 2016 ). For level ‘c) where does it diffuse?’, the modeling approaches to depict the underlying (social) structure range from diffusion or exchange on a grid or von Neumann neighborhood to complex network architectures (e.g., random, small-world, scale-free).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…13Note that alternative conceptualizations of endogenous absorptive capacity have also been proposed, for example, by Klaus Wersching (2010) or Ivan Savin and Abiodun Egbetokun (2016). …”
mentioning
confidence: 99%